Contrasting Root and Photosynthesis Traits in a Large-Acreage Canadian Durum Variety and Its Distant Parent of Algerian Origin for Assembling Drought/Heat Tolerance Attributes - Ashe, Paula; Shaterian, Hamid; Akhov, Leonid; Kulkarni, Manoj; Selvaraj, Gopalan (Frontiers in Chemistry, 2017)
In Canada, the world’s top exporter of high-protein durum, varietal development over its nearly six-decade history has been driven by a quest for yield improvement without compromise on grain protein content and other quality aspects. Pelissier, a landrace selection from Algeria that was introduced into North America more than a century ago and the variety Strongfield that was released in 2004 are notable. Pelissier, known to elaborate more roots and considered as drought tolerant, has been cultivated commercially and thus deemed adapted. Strongfield has Pelissier in its pedigree, and it remains a high-acreage variety. Strongfield was found to elaborate only about half of the root biomass of Pelissier at maturity in greenhouse trials under well-watered conditions. Extended drought stress caused a significant reduction in the root biomass of both lines. However, Pelissier under drought maintained at least as much root biomass as that of Strongfield under well-watered conditions. In comparison to Pelissier, it had a superior photosynthesis rate (27.16 µmol CO2 m-2 s-1), capacity for carboxylation (Vcmax: 132.83 µmol CO2 m-2 s-1) and electron transport/ribulose-1,5--bisphosphate (RuBP) regeneration (Jmax: 265.40 µmol CO2 m-2 s-1); the corresponding values for Pelissier were 19.62 µmol CO2 m-2 s-1, 91.87 µmol CO2 m-2 s-1, and 163.83 µmol CO2 m-2 s-1, respectively, under well-watered conditions. Under short-term/mild drought conditions, the carbon assimilation rate remained stable in Pelissier while it declined in Strongfield to the Pelissier level. However, Strongfield succumbed to extended drought sooner than Pelissier. Photosynthesis in Strongfield but not Pelissier was found to be sensitive to high temperature stress. These results provide encouraging prospects for further exploitation of beneficial physiological traits from Pelissier in constructing climate-resilient, agronomically favourable wheat ideotypes.